1981
DOI: 10.1038/bjc.1981.146
|View full text |Cite
|
Sign up to set email alerts
|

Significance of non-standard Philadelphia chromosomes in chronic granulocytic leukaemia

Abstract: Summary.-One hundred and nineteen unselected and similarly treated patients with Ph1-positive chronic granulocytic leukaemia (CGL) had the precise nature of their chromosome rearrangements producing the Ph1 studied to determine whether this had any clinical relevance. Eighteen (15°,) did not have the usual 9/22 translocation and these, by life-table analysis, had a significantly shorter benign phase of their disease than the others (P<0.01). It further appeared that possession of a nonstandard Ph' was related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
2

Year Published

1982
1982
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(19 citation statements)
references
References 6 publications
0
17
2
Order By: Relevance
“…Our data on the type and frequency of chromosome abnormalities in 106 cases of CML appeared to be somewhat different from those reported by the FIWCL (1978) and some other authors who studied relatively large numbers of CML cases (Lawler et al, 1976;Engel et al, 1977;Seabright and Pearson, 1978;Pasquali et al, 1979;Stoll and Oberling, 1979;Bernstein et al, 1980;Hagemeijer et al, 1980;Kohno and Sandberg, 1980;Sadamori et al, 1980;Fleischman et al, 1981;Potter et al, 1981 ;Oshimura et aI., 1982).…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…Our data on the type and frequency of chromosome abnormalities in 106 cases of CML appeared to be somewhat different from those reported by the FIWCL (1978) and some other authors who studied relatively large numbers of CML cases (Lawler et al, 1976;Engel et al, 1977;Seabright and Pearson, 1978;Pasquali et al, 1979;Stoll and Oberling, 1979;Bernstein et al, 1980;Hagemeijer et al, 1980;Kohno and Sandberg, 1980;Sadamori et al, 1980;Fleischman et al, 1981;Potter et al, 1981 ;Oshimura et aI., 1982).…”
Section: Discussioncontrasting
confidence: 90%
“…Although the overall frequencies of both the standard and variant Ph 1 translocations and other types of chromosome abnormalities in CML have been estimated from time to time (LaMer, 1977;Sonta and Sandberg, 1977;FIWCL, 1978;Rowley, 1980;Sandberg, 1980;MiteIman and Levan, 1981), the number of cases dealt with in most of the reported series seems to be still insufficient to allow reasonable comparison of data among different geographic areas or ethnic groups. In fact, we are aware of only 5 original reports in which more than 100 cases of CML were investigated by banding methods (Seabright and Pearson, 1978;Pasquali et al, 1979;Fleischman et aL, 1981;Potter et aL, 1981;Oshimura et aL, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Two previous studies also noted a shorter survival in variant Ph-positive CML (Potter et al, 1981;Bernstein et al, 1984). Other groups, however, failed to support these findings (Sandberg, 1980;De Braekeleer, 1987).…”
Section: Discussioncontrasting
confidence: 38%
“…Previous survival analyses of variant Ph-positive CML, however, have yielded contradictory results. Several reports have noted a significantly worse prognosis in variant Ph-positive patients than in those with classical t(9;22) (Potter et al, 1981;Bernstein et al, 1984), however, other studies have failed to support this theory (Sandberg, 1980;De Braekeleer, 1987).…”
mentioning
confidence: 84%
“…Second, a variant Ph chromosome was more frequent in patients with a deletion and, although controversial, some previous studies have suggested that such patients have a worse prognosis. 32,33 However this does not account for the survival difference reported here because there was no significant survival difference between patients with classical or variant Ph translocations (median survival 76 months versus 60 months, log-rank P ϭ .15). Moreover, analysis of the subgroup of 200 patients with classical Ph translocations revealed a worse survival for patients with a deletion compared to those without a deletion (median survival 38 versus 81 months, log-rank P ϭ .002).…”
Section: Deletion Status Is a Powerful Prognostic Indicator In CMLmentioning
confidence: 81%